Effect of irrigation and crop geometry on growth, yield, quality and profitability of transplanted fennel (Foeniculum vulgare Mill.) - S K Agrawal, R L Bhardwaj, (Journal of Spices and Aromatic Crops, 2014)
Field experiments were conducted in two adjoining farmer’s field in a tribal area of district Sirohi (Rajasthan) during two successive seasons from July to March, 2011 and 2012 to study the impact of varied crop geometry and irrigation methods on production, quality and profitability of fennel. The trench method of irrigation exhibited significantly higher plant height, number of branches, number of roots plant-1, root length, fresh weight of shoot and roots plant-1, maximum number of umbels plant-1, umbellate umbel-1, number of seed umbel-1, highest seed yield (26.52 q ha-1) with maximum gross return (Rs. 305,714.15), net return (Rs. 266,314.15) and benefit:cost ratio (6.75). Comparatively less time (26.25 h) was required for one hectare irrigation in the same treatment in both the years. The crop planted in paired row (210 cm/120 cm × 25 cm) significantly influenced crop growth, yield and profitability of fennel. In this treatment, highest plant height, number of branches plant-1, number of roots plant-1, root length, fresh weight of shoot and root, maximum number of umbel plant-1, umbellate umbel-1, number of seed umbel-1, highest seed yield (28.55 q ha-1) with maximum gross return (Rs. 336,940.80), net return (Rs. 294,670.80) and benefit: cost ratio (6.97) was observed in both the years. Lower growth, yield and profitability were found in border strip method of irrigation and single row (90 cm × 45 cm) method of planting.